Reinforce Corporate Social Responsibility through Earnings Management - Chrisna Suhendi; Luluk Muhimatul Ifada; Kiryanto Kiryanto (Jurnal ASET (Akuntansi Riset), 2022)
The determinants of companies in applying CSR are leverage and earnings management. Empirical evidence so far has produced conflicting evidence about the relationship between leverage, earnings management, and CSR. This study aims to identify the effect of leverage and earnings management on corporate social responsibility. This study also examines earnings management as a mediating variable. This research was conducted on 179 manufacturing companies for three periods, since 2017-2019. Multiple linear regression method was used to analyze this research. Statistical t-test (partial) was carried out for the used of hypothesis testing. The results of this study indicate that leverage has a negative and significant effect on earnings management. In addition, leverage has a positive and significant impact on corporate social responsibility. The mediation results between leverage on corporate social responsibility through earnings management show that earnings management in this study cannot mediate the relationship between the board of commissioners and leverage on corporate social responsibility. These findings are helpful for investors and policymakers. Investors are advised not to trust companies involved in CSR projects and provide transparent financial reports. Because companies can manipulate earnings and provide less accurate financial reports to shareholders, CSR projects must be assessed for credibility carefully. Thus, policymakers should have some guidelines on actual CSR disclosure, not just statements, because it may deceive stakeholders.